Accurate optical fiber current transducer for high-voltage direct current (HVDC) transmission. Issue 6 (2nd November 2022) - Liu, Haifeng; Guo, Hongjie; Tan, Manqing; Li, Qin; Meng, Xiangqiang; Yang, Xu
Abstract: Accurate optical fiber current transducer based on the Faraday magneto-optical effect is described for high voltage direct current (HVDC) transmission. The transducer may be used to measure DC and high-order harmonic currents in a ± 800 kV DC transmission field. The performance characteristics of sensitivity, non-linearity, temperature stability, and harmonic accuracy of the prototype were investigated. The results show that the scale factor error in the −40 °C to 70 °C range is below ±0.2%. The presented optical fiber current transducer has potential applications for HVDC detection fields, such as for a polarity bus and a converter valve bridge arm.